ICT readiness in teaching and learning as perceived by technical and vocational education teachers in Malaysia - Alazzam, Abu-Obaideh Saleem Saleh (2013)
The purpose of this study was to determine the information and communication technology (ICT) readiness and the use of ICT in teaching by technical and vocational teachers in Malaysia. The questionnaire was developed by the researcher and administered to 329 technical and vocational teachers who were teaching engineering subjects in Malaysian technical and vocational schools. Descriptive and inferential statistic analyses were used to analyze the data such as t-test, ANOVA, MANOVA, Chi-Square, Pearson Product Moment Correlation, and Multiple Discriminant Analysis (MDA). The findings of this study indicated that the majority of the teachers in terms of their readiness had moderate level about ICT knowledge, moderate skillful level about ICT skills, and possessed positive attitudes towards ICT use in teaching. The findings indicated that there were no statistically significant differences of gender, type of training, administrative support and ICT availability with ICT knowledge level. However, there were statistically significant differences of age, years of teaching experience, and level of qualification with ICT knowledge level. While the findings also indicated that there were statistically significant differences of gender, age, years of teaching experience, and type of training with ICT skills level. In addition to that, there were no statistically significant differences on the level of qualification, administrative support, and ICT availability with ICT skills level. Moreover, there was no significant difference between both gender and administrative support with teachers’ attitudes. While, there were no significant differences between attitudes and teachers’ age, years of teaching experience, level of qualification, type of training and ICT availability. The results of MANOVA indicated that there was significant relationship between demographic characteristics by gender only with teachers’ overall readiness (ICT knowledge, ICT skills, and attitudes). However, there were no significant relationship between teachers’ education background and overall support with teachers’ overall readiness. For level of using ICT in teaching among the teachers, the majority of teachers indicated to be using ICT very frequently with heavy users’ level. Moreover, only one variable, that is, level of qualification appeared to have some influence on the teachers’ ICT use in teaching. Only those with a bachelor degree tend to use ICT more frequently than the others. The results of correlations measured were significantly positive between ICT use and ICT skills as well as ICT use and attitudes. The correlation also was positive between ICT skills and attitudes. The results of Multiple Discriminant Analysis (MDA) found that the variables ICT skills and attitudes were the best predictors among other variables in ICT use.